Konstribisi Khotmil Qur’an dalam Meningkatkan Motivasi Belajar Membaca Al-Qur’an di MA Darul Faizin Assalafiyah Catak Gayam Mojowarno Jombang - Mustofa, Ali (Ali Muchasan, 2019)
This research discusses the less of students’ motivation in reading al qur’an as khotmil qur’an activity at MA Darul Faizin Assalfiyah Catak Gayam Mojowarno. The research result shows that this activity increased students’s motivation to learn especially in reding al qur’an. The head master supported it by giving reward to the class that was active in joing the khotmil qur’an activity, and punished those who did not join it. This activity contributed to students’ smoothness in reading al qur’an. Khotmil qur’an is done twice a week in rotation from class to another. And the students’ motivation is proved by their willingness to smoothen the reading of al qur’an becauseof the reward and punishment, and they also want to strngthens the kinship.